2020
DOI: 10.1242/bio.053322
|View full text |Cite
|
Sign up to set email alerts
|

Communication between Cyclin dependent kinase Cdc2 and the Wis1-Spc1 MAPK pathway determines mitotic timing in Schizosaccharomyces pombe

Abstract: Checkpoint activation and gene expression modulation represent key determinants of cellular survival in adverse conditions. The former is regulated by cyclin-dependent kinases (CDKs) while the latter can be controlled by mitogen-activated protein kinases (MAPKs). Association between cell-cycle progression and MAPK-dependent gene expression exists in cells growing in optimal environments. While MAPK-mediated regulation of the cell cycle is well characterised, the reciprocal influence of mitotic CDK on stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We therefore decided to investigate whether the trends of altered cell fate upon glucose to lactate shift could be associated with any differences in Sty1 activity of these cells. Sty1 activity is known to be high in cdc2-3w cells compared with wt cells in normal conditions ( Ghosal et al, 2020 ), and we found that lactate shift causes a higher increase in Sty1 phosphorylation in cdc2-3w cells ( Fig. 3A,B ) than in wt cells ( Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…We therefore decided to investigate whether the trends of altered cell fate upon glucose to lactate shift could be associated with any differences in Sty1 activity of these cells. Sty1 activity is known to be high in cdc2-3w cells compared with wt cells in normal conditions ( Ghosal et al, 2020 ), and we found that lactate shift causes a higher increase in Sty1 phosphorylation in cdc2-3w cells ( Fig. 3A,B ) than in wt cells ( Fig.…”
Section: Resultssupporting
confidence: 52%
“…Cdc2 can be activated by the dephosphorylation of its Y15 residue by the Cdc25 phosphatase ( Ducommun et al, 1990 ), and Sty1 is known to be able to negatively regulate Cdc25 ( Paul et al, 2018 ). Moreover, aberrant Cdc2 activity leads to increased Sty1 phosphorylation ( Paul et al, 2018 ), while inhibition of Cdc2 leads to decreased Sty1 phosphorylation ( Ghosal et al, 2020 ) and the Wis1 MAPKK is a mediator of this communication ( Ghosal et al, 2020 ). We also earlier reported that Sty1 is important for regulating functions of the APC ( Basu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…3A,C). Given that we have earlier reported that Spc1 activity in this cells is high [30], this was not surprising as Spc1 is known to cause increased Atf1 expression [17]. The most significant aspect of this observation, however, is that in the presence of a hyperactive Cdc2, the increased Atf1 levels were leading to decreased Cdc13 accumulation.…”
Section: Resultsmentioning
confidence: 80%
“…We then wanted to understand how these temporal changes in Spc1 activity are brought about. We have recently reported a connection between Spc1 and Cdc2 activities during mitotic timing decisions in S. pombe cells [30]. Metaphase to Anaphase transition is a well‐known outcome of mitotic cyclin‐dependent kinase (CDK)‐dependent activation of the APC [31].…”
Section: Resultsmentioning
confidence: 99%
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Agamani Ghosal is first author on ‘ Communication between Cyclin dependent kinase Cdc2 and the Wis1-Spc1 MAPK pathway determines mitotic timing in Schizosaccharomyces pombe ’, published in BiO. Agamani is a PhD student in the Cell Division lab of Dr Geetanjali Sundaram.…”
mentioning
confidence: 99%